Penggunaan lemak fleshing industri penyamakan kulit untuk pembuatan sabun mandi - Sunaryo, Ignatius; Sutyasmi, Sri; Widari, Widari; Murwati, Murwati (Majalah Kulit, Karet, dan Plastik, 2002)
An experimentation the Use of Fat from Fleshing of Leather Tanning Industry to Produce Bath Soap was aimed to use the fat from fleshing to gain the alternative source of basic material for bath soap, to assist the industry to solve the environmental pollution and increasing the population income. The point to be gained after finishing this experiment was to find out the problem solving of environmental pollution problem caused by fleshing from leather tanning industry. Goat/sheep fleshing from one of leather tannings in Yogyakarta was collected and had been used as a source of fat. Fat from fleshing was produced by 3 kinds of heating those were coocked, âkukusâ, and steam. The results of fat analysis showed that the average of saphonification value was 201.01; free faty acid value was 0.86%; acid value was 1.72 and the unsaphonification fat value was 1.44%. The variations of fat used for bath soap manufacture were 55%, 60%, 65%, 70% and 75%; whereas the variations of sodium hydrokside were 11, 14, 17. 20 and 23, each of which was in parts. The result of this experiment showed that the fat from fleshing could be a source of fat and could be used for bath soap manufacture. In such way, it could be as a pollultion problem solving to the industry. The result of bathÂ  soap analysis showed that almost all of the variations of fat and sodium hydrokside could meet the SNI 06-3532-1994 about bath soap. Economically point of view showed that the value of producing fat in various regions such as Jabotabek, West Java, Center Java, DIY and East would vary from Rp6,000,000,- to Rp.200,000,000,-; whereas the value of producing bath soap would vary from Rp 21,000,000,- - Rp 700,000,000,-Â Key words: fleshing, fat, soap, environment, tannery, waste management.Â